Controlled Self-Assembly inside C-Shaped Polyaromatic Strips - Sharafi, Mona; Weinert, Zackariah J.; Cohen, Ian M.; Liao, Chenyi; Ivancic, Monika; Li, Jianing; Schneebeli, Severin T. (Synlett, 2016)
Chirality-assisted synthesis (CAS) embodies a powerful strategy for the creation of chiral molecules with well-defined shapes and large cavities. In this communication, we show that C-shaped molecular receptors created with this approach bind to stacks of amphipathic perylenediimide (PDI) dyes. Evidence from 1H NMR titrations, DOSY-NMR studies, and all-atom molecular dynamics simulations indicates that – in the preferred supramolecular binding mode – such polyaromatic strips specifically recognize stacked PDI dimers in solution. These results represent a key step toward the controlled self-assembly of dye molecules inside chiral cavities of shape-persistent, polyaromatic strips.
Keywords: supramolecular chemistry; chirality-assisted synthesis; polyaromatic molecular strips; perylene dyes